The mental health challenges, especially suicidality, experienced by women during perimenopause and menopause: A qualitative study - Olivia Hendriks; Jason C. McIntyre; Abigail K. Rose; Clair Crockett; Louise Newson; Pooja Saini (Women's Health)
Background: Menopause, characterised by significant hormonal changes, can greatly impact mental health. While physical symptoms are well-known, the psychological effects, particularly suicidality, are underexplored. Suicide rates among women aged 45–55, the typical menopausal transition age, are notably higher, potentially linked to hormonal fluctuations that affect mood regulation. Despite this, little qualitative research exists on the relationship between perimenopause and mental health challenges, including suicidality. Objectives: This study explores the mental health challenges, especially suicidality, experienced by women during perimenopause and menopause. It seeks to understand the factors contributing to these experiences and the role of healthcare in addressing them. Design: Qualitative semi-structured interviews explored women’s experiences of perimenopause and menopause, with a particular focus on mental health challenges including suicidality. The interviews were conducted and spanned from March 2023 to February 2024. Method: Semi-structured interviews were conducted with 42 women, recruited from a private menopause clinic and the general population. Interviews, lasting 30–45 min, explored participants’ mental health experiences during perimenopause and menopause. Data were analysed using reflexive thematic analysis, with NVivo 14 used for data management. Results: Participants reported varying degrees of suicidality from abstract thoughts to suicide attempts. Feelings of hopelessness and entrapment were common triggers. Delays in receiving appropriate hormone replacement therapy (HRT) and misdiagnoses, such as being prescribed antidepressants instead of HRT, worsened symptoms. Women reported significant improvements in mental well-being after receiving timely HRT. Peer support and lifestyle changes were also identified as beneficial. Conclusions: Improved training for healthcare providers, timely HRT access and holistic care are crucial for addressing perimenopausal mental health challenges. Women’s Health Hubs, as outlined by the Women’s Health Strategy for England, offer a potential solution for integrated care.